Exploring current undergraduate student perspectives on the introduction of the degree apprenticeship scheme in diagnostic radiography – a single institution study. Issue 4 (November 2022) - Green, D.; Heales, C.J.; Hughes, D.; Marsden, A.; Mills, J.A.
Abstract: Introduction: The first degree apprenticeship programme in diagnostic radiography was launched in March 2020. This route into radiography runs in parallel with 'conventional' pre-registration programmes where students apply to a higher education institution (HEI) and undertake discrete clinical placements. The aim of this study was to explore the perspectives of pre-registration students on the diagnostic radiographer degree apprenticeship route. Methods: A qualitative approach (online questionnaire) gathered attitudes and opinions of pre-registration students from a single HEI, regarding the degree apprenticeship programme. Participants were pre-registration medical imaging students from all stages of the programme (n = 204). Braun and Clarks's thematic analysis was employed for data analysis. Results: A response rate of 21% (n = 44) was recorded. Four themes emerged from data analysis: (1) misunderstandings surrounding the degree apprenticeship, (2) financial implications and (3) practical experience associated with both degree courses and (4) the experience the pre-registration degree has to offer. Conclusion: There was an apparent lack of understanding regarding the degree apprenticeship leading students to misinterpret aspects of the course. Additionally, students highlighted the earning aspect of the apprenticeship to be an advantage in comparison to student debts associated with the traditional pre-registration programmes. Furthermore, students emphasised the advantage of the clinical focus practice associated with the degree apprenticeship. Nevertheless, students who have selected the HEI route still value what the traditional pre-registration degree offers. Implications for practice: As degree apprenticeship programmes become widely available, a greater awareness should, therefore, follow. In the interim, there is scope for HEIs to seek to raise awareness of degree apprenticeship provision. HEIs should seek to allay any concerns and highlight the benefits of having this alternative route into the profession.